A reassessment of Melanophidium Günther, 1864 (Squamata: Serpentes: Uropeltidae) from the Western Ghats of peninsular India, with the description of a new species - Gower, David J.; Giri, Varad; Captain, Ashok; Wilkinson, Mark (Zootaxa, 2016)
A new species of the uropeltid snake genus, Melanophidium Günther, 1864 is described based on a series of eight specimens. Melanophidium khairei sp. nov. is the fourth species described in the genus, and the first for 144 years. Superficially M. khairei sp. nov. resembles M. punctatum Beddome, 1871 in being piebald and punctate (and it was previously misidentified as M. punctatum), but in many scalation characters it more closely resembles M. wynaudense (Beddome, 1863). The new species occurs in southern Maharashtra, Goa, and northern Karnataka, in the Western Ghats region of peninsula India. It is the most northerly member of its genus. Lectotypes and paralectotypes are designated for M. wynaudense, M. bilineatum Beddome, 1870, and M. punctatum. A new key to the species of Melanophidium is presented. Aspects of the morphology, taxonomy and distribution of the three previously described species of Melanophidium are reviewed and revised.